Developmental Neurotoxicity of Fipronil and Rotenone on a Human Neuronal In Vitro Test System - Anne Schmitz; Silke Dempewolf; Saime Tan; Gerd Bicker; Michael Stern (Neurotoxicity Research, 2021)
Pesticide exposure during in utero and early postnatal development can cause a wide range of neurological defects. However, relatively few insecticides have been recognized as developmental neurotoxicants, so far. Recently, discovery of the insecticide, fipronil, in chicken eggs has raised public concern. The status of fipronil as a potential developmental neurotoxicant is still under debate. Whereas several in vivo and in vitro studies suggest specific toxicity, other in vitro studies could not confirm this concern. Here, we tested fipronil and its main metabolic product, fipronil sulfone both at concentrations between 1.98 and 62.5 µM, alongside with the established developmental neurotoxicant, rotenone (0.004–10 µM) in vitro on the human neuronal precursor cell line NT2. We found that rotenone impaired all three tested DNT endpoints, neurite outgrowth, neuronal differentiation, and precursor cell migration in a dose-dependent manner and clearly separable from general cytotoxicity in the nanomolar range. Fipronil and fipronil sulfone specifically inhibited cell migration and neuronal differentiation, but not neurite outgrowth in the micromolar range. The rho-kinase inhibitor Y-27632 counteracted inhibition of migration for all three compounds (EC50 between 12 and 50 µM). The antioxidant, n-acetyl cysteine, could ameliorate the inhibitory effects of fipronil on all three tested endpoints (EC 50 between 84 and 164 µM), indicating the involvement of oxidative stress. Fipronil sulfone had a stronger effect than fipronil, confirming the importance to test metabolic products alongside original pesticides. We conclude that in vitro fipronil and fipronil sulfone display specific developmental neurotoxicity on developing human model neurons.

A locust embryo as predictive developmental neurotoxicity testing system for pioneer axon pathway formation - Karsten Bode; Maja Bohn; Jennifer Reitmeier; Philine Betker; Michael Stern; Gerd Bicker (Archives of Toxicology, 2020)

Regeneration of axotomized olfactory neurons in young and adult locusts quantified by fasciclin I immunofluorescence - Hannah Wasser; Alexandra Biller; Georgios Antonopoulos; Heiko Meyer; Gerd Bicker; Michael Stern (Cell and Tissue Research, 2017)

Olfactory pathway in Xibalbanus tulumensis: remipedian hemiellipsoid body as homologue of hexapod mushroom body - Torben Stemme; Thomas M. Iliffe; Gerd Bicker (Cell and Tissue Research, 2016)

Human Ntera2 cells as a predictive in vitro test system for developmental neurotoxicity - Michael Stern; Andrea Gierse; Saime Tan; Gerd Bicker (Archives of Toxicology, 2014)

Cellular phenotypes of human model neurons (NT2) after differentiation in aggregate culture - Grzegorz Podrygajlo; Million A. Tegenge; Andrea Gierse; Francois Paquet-Durand; Saime Tan; Gerd Bicker; Michael Stern (Cell and Tissue Research, 2009)

Mixed cholinergic/glutamatergic neuromuscular innervation of Onychophora: a combined histochemical/electrophysiological study - Michael Stern; Gerd Bicker (Cell and Tissue Research, 2008)

Cellular expression patterns of acetylcholinesterase activity during grasshopper development - Gerd Bicker; Mario Naujock; Annely Haase (Cell and Tissue Research, 2004)

Sources and targets of nitric oxide signalling in insect nervous systems - Gerd Bicker (Cell and Tissue Research, 2001)